Describing interest-only mortgage borrowers' savings and spending using Danish register data - Henrik Yde Andersen; Stine Ludvig Bech (Danmarks Nationalbank, 2024)
Interest-only mortgages (IOMs) were popular before the 2007-2008 financial crisis, e.g. in the US and UK, and remain common in a few countries today, including the Netherlands, Sweden and Denmark. We use Danish administrative data, covering all mortgage loans originated between 2010 and 2019, to compare savings and spending of IOM borrowers to that of non-IOM borrowers using their mortgage origination year in an event study design. Conditional on time and individual fixed effects, we show that homeowners aged 50 and above increased spending in connection with taking out an IOM, while homeowners below this age predominantly accelerated non-mortgage debt repayments.
Keywords: G51; D14; 330; Mortgage; interest-only; deferred amortisation; savings behaviour